2003
DOI: 10.1177/1049732302250759
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the Community: Gaining Insider Perspectives From the Outside

Abstract: Accessing participants for research projects is often treated as unproblematic. However the experience outlined here of negotiating access to participants within a community setting illustrates the inherent difficulties of recruitment. The authors describe the techniques used and practical challenges faced when accessing participants within a socially deprived community for a qualitative research project on social capital. They used a number of different strategies to generate a diverse sample including advert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
150
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 8 publications
0
150
0
1
Order By: Relevance
“…Widespread implementation of the participatory research model in mental health and medical research can clearly play a key role in reducing health disparities. The communitybased participatory model in which all stakeholders of a community being studied are invited and encouraged to take part in all phases of a research study is an ethical and effective way of conducting mental health research, especially with members of underserved communities (Minkler & Wallerstein, 2003;Sixsmith, Boneham, & Goldring, 2003;Macaulay et al, 1999; Agency for Healthcare Research and Quality [AHRQ], 2003).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Widespread implementation of the participatory research model in mental health and medical research can clearly play a key role in reducing health disparities. The communitybased participatory model in which all stakeholders of a community being studied are invited and encouraged to take part in all phases of a research study is an ethical and effective way of conducting mental health research, especially with members of underserved communities (Minkler & Wallerstein, 2003;Sixsmith, Boneham, & Goldring, 2003;Macaulay et al, 1999; Agency for Healthcare Research and Quality [AHRQ], 2003).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Widespread implementation of the participatory research model in mental health and medical research can clearly play a key role in reducing health disparities. The communitybased participatory model in which all stakeholders of a community being studied are invited and encouraged to take part in all phases of a research study is an ethical and effective way of conducting mental health research, especially with members of underserved communities (Minkler & Wallerstein, 2003;Sixsmith, Boneham, & Goldring, 2003;Macaulay et al, 1999; Agency for Healthcare Research and Quality [AHRQ], 2003).Mental health researchers are recognizing the importance of asking communities to set the agenda and context for appropriate, respectful research. Research that starts "where the people are" has demonstrated that when the realities of community life become an integral part of the process, study results directly address the needs of the target community (Israel, Schulz, Parker, & Becker, 1998; Macauley et al, 1999;Minkler & Wallerstein, 2003;Sixsmith, Boneham, & Goldring, 2003).…”
mentioning
confidence: 99%
“…The project interviewers were all women, but we differed in terms of social class, ethnicity, age and reproductive/family situation (among other things). The specific configurations and intersection of identity and experience, in relation to our research participants, meant that we all spanned an insider/outsider spectrum in complex and shifting ways, as we describe below (see also Mullings, 1999;Brah and Phoenix, 2004;GressgĆ„rd, 2008), shaping the emergence of narratives and interpretations (Sixsmith et al, 2003;Thomas, Blacksmith and Reno, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Oakley 1981;Standing 1998;Sibley 1995;Sixsmith et al 2003;Emmel et al 2007). Feminist geographers have been particularly concerned to explore and theorise feminist 'ways of knowing' and epistemologies in order to discern gender-based disadvantage and particular knowledges from the standpoint of women (Gibson-Graham 1994;Harding 1998;Rose 1993Rose , 1997.…”
Section: Introductionmentioning
confidence: 99%